Implementasi Sistem Informasi Persediaan Barang pada UMKM untuk Mengurangi Kerugian Akibat Ketidak Terpantauan Stok - Muhammad Abdul Wahid; Ratna Sari Dewi (Ekliptika, 2026)
Sanfat is a company that produces Jamu Sinom drinks from traditional ingredients. The company often has difficulty finding turmeric raw materials. When this happens, it will certainly increase the cost of producing Jamu Sinom. For this reason, it is necessary to control raw materials using the Material Requirement Planning (MRP) method and Moving Average Forecast to determine future raw materials. During this period, the company purchased an average of 75.0 kg. The order cost is Rp.160,000 and the storage cost is Rp.500,000. The total cost of raw material inventory in 1 year is Rp. 11,600,000. Based on the calculations and analysis carried out using the Material Requirement Planning (MRP) method with lot sizing techniques, namely lot-for-lot and Economic Order Quantity (EOQ). The lot-for-lot calculation resulted in a total cost of Rp. 17,820,000 and the EOQ calculation resulted in a total cost of Rp. 8,140,000. The minimum raw material order is EOQ, which can be used as a solution for raw material control for Sinom herbal products at UD. Sanfaat.